2009
DOI: 10.21608/kvmj.2009.108724
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemio-Coprological Study of Protozoan and Nematode Parasites of Ruminants in Tropical Semi-Arid District of Somaliland (Northern of Somalia)

Abstract: The present study showed that the prevalence of gastrointestinal parasites in overall studied ruminants (cattle, sheep and goats) where highest with Trichsrtongylus Axei 26.9% (n=343), Lungworm (Dictyocaulus spp.) 9.8%, (n= 125), Eimeria (Coccidia) 7.2% (n=92), Ascaris (Neoscaris vitulorum) 3.6% (n=14), and Homonchus contortus 2.3% (n=30) respectively. For cattle, the overall prevalence was 30.9% (n=120) with highest by Trichsrtongylus Axei 22.9% (n=89), Ascaris 3.6% (n=14), Lungworm 2.3% (n=9) and Homonchus 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
2
1
1
Order By: Relevance
“…The present study agrees with the previous studies conducted in different parts of the world with higher prevalence in females than male [30,31,32]. However, different studies reported a higher prevalence in male than female animals [19,33,34,35]. Some of the previous studies gave notion that females are more prone to helminthes (nematodes) infestation compared to male small ruminant.…”
Section: Discussionsupporting
confidence: 92%
“…The present study agrees with the previous studies conducted in different parts of the world with higher prevalence in females than male [30,31,32]. However, different studies reported a higher prevalence in male than female animals [19,33,34,35]. Some of the previous studies gave notion that females are more prone to helminthes (nematodes) infestation compared to male small ruminant.…”
Section: Discussionsupporting
confidence: 92%
“…In this study when comes to the sex there were no significant variation was observed between male and female despite slightly higher infection noticed in female sheep with 69.3% female and 63.1% male respectively. There was no statistical association between sex and prevalence of gastro intestinal nematodes agree with that of Abdurezaq, Regassa & Ghanem [7,17,29]. This also agrees with report by Assefa & Sissay [30].…”
Section: Journal Of Dairy and Veterinary Sciencessupporting
confidence: 91%
“…However, it was higher than the reports of 26.8% [42] and 1.03% [43], the 2.3% prevalence from Somaliland [44], and the finding of Yimer and Birhan [45] and much higher The variations in the prevalence of hemonchosis in sheep in different parts of Ethiopia and different countries are attributed to different factors, such as environmental factors (e.g., geoclimatic factors), sample size, host factors (e.g., natural resistance) [47], and the standard of management (e.g., habits of anthelmintic usage and nutrition) [48], which influence the development, distribution, and extended survival of the infective larval stage of the parasite [49].…”
Section: Discussioncontrasting
confidence: 66%